NH3-SCR (selective catalytic reduction) catalyst as well as preparation method and application thereof

By doping metal elements into acidic zeolites, the problem of narrow reaction window and poor stability of NH3-SCR catalysts is solved, and the high-temperature oxidation and low-temperature activity of the catalyst is improved, and its application scope is broadened.

CN119869599APending Publication Date: 2025-04-25SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311373046.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-23
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing NH3-SCR catalysts have problems with narrow reaction windows and low hydrothermal stability, which limits their application range.

Method used

Acid zeolite modified with metal elements is used as catalysts to form metal nanoclusters by doping metal elements such as Fe, Cu, Mn and Zn in the acidic zeolite to improve the low-temperature activity and high-temperature oxidation properties of the catalyst.

Benefits of technology

It significantly broadens the reaction window of the catalyst, improves the thermal stability and hydrothermal stability of the catalyst, and enhances its application ability in automotive exhaust purification.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869599A_ABST
    Figure CN119869599A_ABST
Patent Text Reader

Abstract

The invention relates to an NH3-SCR (selective catalytic reduction) catalyst as well as a preparation method and application thereof. The NH3-SCR catalyst comprises: a metal element modified acidic zeolite; preferably, the existence form of the metal elements in the metal element modified acidic zeolite is a metal nano-cluster.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an NH3-SCR catalyst and a preparation method and application thereof, belonging to the field of environmental catalysis. Background Art

[0002] Selective catalytic reduction (SCR) technology for reducing NOx with NH3 has been commercially applied in stationary source combustion devices, but its narrow reaction window and low hydrothermal stability have greatly limited its application.

[0003] Zeolite molecular sieve is a nanomaterial with a large specific surface area and a regular microporous structure. Zeolite has excellent low-temperature adsorption and high-temperature desorption properties. Among them, aluminum-containing zeolite has certain acidic sites, which can improve the high-temperature activity of NH3-SCR. Zeolites doped with metal elements such as Cu, Fe, and Mn have abundant oxygen vacancies, which give them excellent catalytic oxidation activity. They can greatly improve the low-temperature activity of the catalyst to a certain extent, thereby expanding the reaction window of the NH3-SCR catalyst. In addition, zeolite molecular sieve catalysts have excellent thermal stability and thermal stability, and are an excellent choice for reducing NOx in the National VI stage. Summary of the invention

[0004] In view of the above problems, the present invention aims to provide an NH3-SCR catalyst and a preparation method and application thereof.

[0005] In a first aspect, the present invention provides an NH3-SCR catalyst, the NH3-SCR catalyst comprising: an acidic zeolite modified by a metal element; Preferably, the metal element in the metal element-modified acidic zeolite exists in the form of metal nanoclusters.

[0006] Preferably, the acidic zeolite includes TS-1, ZSM-5 or Beta zeolite.

[0007] Preferably, the metal element in the metal element-modified acidic zeolite is at least one of Fe, Cu, Mn and Zn, and the content of the metal element is 1.23. to 5.79 wt.%;

[0008] In a second aspect, the present invention provides a method for preparing an NH3-SCR catalyst. When the NH3-SCR catalyst is an acidic zeolite doped with metal ions, the preparation method comprises: dissolving a titanium source or an aluminum source (ZSM-5, Beta is an aluminum source, TS-1 is a titanium source), an inorganic silicon source, a metal element source, and an alkali metal salt in an aqueous solution containing a structure directing agent to obtain a mixed solution, performing a hydrothermal crystallization treatment, and then filtering, washing, drying and calcining to obtain an acidic zeolite doped with metal elements.

[0009] Preferred ones include: (1) adding an inorganic silicon source and an alkali metal salt to an aqueous solution containing a structure directing agent to obtain a solution 1; (2) adding one of the titanium source or the aluminum source and the metal element source solution to water to obtain solution 2; (3) Solution 2 is added dropwise to solution 1 and stirred to mix, followed by hydrothermal crystallization treatment, and then filtered, washed, dried and calcined to obtain metal element-doped acidic zeolite.

[0010] Preferably, the metal element source is at least one of ferrous chloride, cuprous chloride and zinc sulfate.

[0011] Preferably, the structure directing agent is one of tetrapropylammonium hydroxide (TPAOH) and tetraethylammonium hydroxide (TEAOH).

[0012] Preferably, the silicon source is one of ethyl orthosilicate, orthosilicic acid, and sodium silicate; The aluminum source is one of aluminum sulfate, aluminum chloride, and metaaluminate; The alkali metal salt is one of sodium chloride and potassium chloride.

[0013] Preferably, the concentration of the alkali metal salt in the mixed solution is 1 to 3 mg / mL; The concentration of the metal element in the mixed solution is 10 to 100 mg / mL; The Si / Al atomic ratio in the zeolite precursor solution in the mixed solution is 10 to 100; The temperature of the hydrothermal crystallization is 100 to 220° C., and the time of the hydrothermal crystallization is 12 to 24 hours.

[0014] Preferably, the drying temperature is 80-120° C.; the calcining temperature is 500-600° C., and the calcining time is 4-8 hours.

[0015] In a third aspect, the present invention provides a method for preparing an NH3-SCR catalyst. When the NH3-SCR catalyst is an acidic zeolite modified by a metal element, the preparation method comprises: The acidic zeolite is added to an aqueous solution containing a metal element source and stirred to obtain a mixture; the obtained mixture is washed and centrifuged to remove the upper aqueous solution, and then dried and calcined to obtain the metal element modified acidic zeolite.

[0016] Preferably, the preparation method of the acidic zeolite comprises: dissolving an inorganic silicon source, an aluminum source, and an alkali metal salt in an aqueous solution containing a structure directing agent, performing a hydrothermal crystallization treatment, and then filtering, washing, drying, and calcining to obtain the acidic zeolite.

[0017] Preferably, the metal element source is at least one of ferrous chloride, cuprous chloride and zinc sulfate.

[0018] Preferably, the structure directing agent is one of tetrapropylammonium hydroxide (TPAOH) and tetraethylammonium hydroxide (TEAOH).

[0019] Preferably, the silicon source is one of ethyl orthosilicate, orthosilicic acid, and sodium silicate; The aluminum source is one of aluminum sulfate, aluminum chloride, and metaaluminate; The alkali metal salt is one of sodium chloride and potassium chloride.

[0020] Preferably, the drying temperature is 80-120° C.; the calcining temperature is 500-600° C., and the calcining time is 4-8 hours.

[0021] In a fourth aspect, the present invention provides an application of an NH3-SCR catalyst in automobile exhaust purification.

[0022] Beneficial effects of the present invention: The composite zeolite NH3-SCR catalyst prepared by the present invention not only has a simple synthesis method, but also significantly improves the problems of narrow reaction window and poor catalyst stability of traditional NH3-SCR catalysts, thus providing a basis for the practical application of zeolite catalysts. The present invention provides a method for preparing an NH3-SCR catalyst, which is an aluminum-doped zeolite composite catalyst modified by metal elements. The intrinsic acidity of the aluminum-doped zeolite is used to improve the high-temperature oxidizability of the catalyst, and the redox performance of the metal element is used to improve the low-temperature activity of the catalyst, thereby broadening the reaction activity window. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 XRD patterns of the zeolite catalysts obtained in Example 1, Example 2 and Example 3; H2-TPR and NH3-TPD curves; Figure 2 This is a SEM image of the composite zeolite catalyst prepared in Example 2; Figure 3 This is a TEM image of the composite zeolite catalyst prepared in Example 2; Figure 4 NH3-SCR performance of the zeolite catalysts obtained in Example 1, Example 2 and Example 3. DETAILED DESCRIPTION

[0024] The present invention is further described below by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.

[0025] In the present disclosure, the catalyst is a composite zeolite catalyst including an acidic zeolite modified with a metal element.

[0026] In an optional embodiment, the metal element in the aluminum-doped acidic zeolite is one or more of Fe, Cu, Mn, Zn, etc., preferably Cu ions.

[0027] In an embodiment of the present invention, the metal element modified acidic zeolite is obtained by hydrothermal crystallization at a certain temperature. The acidic zeolite is exemplified by ZSM-5 zeolite, and the acidic zeolite is exemplified by the acidic zeolite modified with Cu. The preparation method of the catalyst is exemplified below.

[0028] Acidic zeolite ZSM-5 is prepared by hydrothermal crystallization. Specifically, an inorganic silicon source, an aluminum source, and an alkali metal salt are dissolved in an aqueous solution containing a structure directing agent, tetrapropylammonium hydroxide (TPAOH), and hydrothermally reacted at 120 to 200°C for 12 to 24 hours. Then, the aluminum-doped ZSM-5 zeolite is obtained by filtration, washing, drying, and calcination. The concentration of the alkali metal salt in the zeolite precursor solution can be 1 to 3 mg / mL. The Si / Al atomic ratio in the zeolite precursor solution can be 15 to 50. The drying temperature can be 80 to 120°C. The calcination temperature can be 500 to 600°C, and the time can be 6 to 8 hours.

[0029] A one-step hydrothermal crystallization method is used to prepare the acidic zeolite modified by metal elements. Specifically, an inorganic silicon source, a titanium source, a corresponding metal source doped with metal elements, and an alkali metal salt are dissolved in an aqueous solution containing a structure directing agent, tetrapropylammonium hydroxide (TPAOH), reacted for a period of time, transferred to a hydrothermal kettle, and hydrothermally reacted at 120 to 200°C for 12 to 24 hours. Then, after filtering, washing, drying, and calcining, the acidic zeolite modified by metal elements of the present invention is obtained. Among them, the concentration of the metal precursor solution can be 10 to 100 mg / mL, the drying temperature can be 80 to 120°C, the calcination temperature can be 500 to 600°C, and the time can be 6 to 8 hours.

[0030] It should be noted that the zeolite composite catalyst is applicable to the above-mentioned method for preparing the catalyst. The composite catalyst obtained in the present invention includes an acidic zeolite modified by a metal element, and the obtained catalyst has excellent catalytic activity and stability, and can be applied to the fields of thermal catalysis and environmental catalysis.

[0031] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values ​​​​exemplified below.

[0032] Example 1 (1) 50 mmol of orthosilicic acid and 0.09 g of potassium chloride were dissolved in 6 mL of H2O and 14.4 g of tetrapropylammonium hydroxide (TPAOH, 25 wt%) aqueous solution, and stirred continuously at 40°C for 4 h to obtain solution 1; (2) Then 1 mmol of sodium aluminate was dissolved in 2 mL of H2O to obtain solution 2; (3) Solution 2 was then added dropwise to solution 1, and the mixture was vigorously stirred at 40°C for 4 h before being transferred to a hydrothermal reactor and hydrothermally treated at 160°C for 18 h; (4) Finally, the mixture was washed twice with a mixed solution of ethanol and water, the upper aqueous solution was removed by centrifugal separation, dried in a drying oven at 100° C. overnight, and then calcined at 550° C. for 4 h to obtain zeolite ZSM-5.

[0033] Example 2 (1) 50 mmol of orthosilicic acid, 0.06 g of potassium chloride and 0.03 g of sodium chloride were dissolved in 6 mL of H2O and 12 g of tetrapropylammonium hydroxide (TPAOH, 25 wt%) aqueous solution, and stirred continuously at 40°C for 4 h to obtain solution 1; (2) Then 2 mmol of titanium sulfate and 0.2 mmol of cuprous chloride were dissolved in 4 mL of H2O to obtain solution 2; (3) Solution 2 was then added dropwise to solution 1, stirred vigorously at 40 °C for 4 h, and then transferred to a hydrothermal reactor for hydrothermal crystallization at 150 °C for 24 h; (4) The mixture was cooled to room temperature, washed with ethanol and water, the upper aqueous solution was removed by centrifugal separation, dried in a drying oven at 80° C. overnight, and then calcined at 550° C. for 4 h to obtain copper-modified zeolite Cu@ZSM-5. In the copper-modified zeolite Cu@ZSM-5 in Example 2, the copper element exists in the form of metal nanoclusters, and the doping content is 3.68 wt. 1%.

[0034] Example 3 (1) 10 g of the zeolite ZSM-1 obtained in Example 1 was added to 100 mL of H2O containing 0.2 mmol of cuprous chloride, and then vigorously stirred at 60°C for 4 h; (2) The mixture was cooled to room temperature, washed with ethanol and water, the upper aqueous solution was removed by centrifugation, dried in a drying oven at 80°C overnight, and then calcined at 550°C for 4 hours to obtain copper-modified acidic zeolite Cu / TS-1. In this Example 3, the copper ion-modified zeolite Cu / TS-1 has a copper element in the form of metal nanoclusters and a doping content of 3.72 wt.%.

[0035] Example 4 The preparation process of the NH3-SCR catalyst in Example 4 is similar to that in Example 2, except that in step (2), 2 mmol of titanium sulfate and 0.05 mmol of cuprous chloride are dissolved in 4 mL of H2O to obtain solution 2. In the copper-modified zeolite Cu@ZSM-5 in Example 4, the copper element exists in the form of metal nanoclusters and the doping content is 1.23 wt. 1%.

[0036] Example 5 The preparation process of the NH3-SCR catalyst in Example 5 is similar to that in Example 2, except that: in step (2), 2 mmol of titanium sulfate and 0.5 mmol of cuprous chloride are dissolved in 4 mL of H2O to obtain solution 2. In the copper-modified zeolite Cu@ZSM-5 in Example 5, the copper element exists in the form of metal nanoclusters and metal nanoparticles, and the doping content is 5.68 wt.%.

[0037] Example 6 100 mg of the catalyst prepared in Examples 1-5 was respectively loaded into a fixed bed quartz reactor and dried at 150°C for 1 h. The reaction raw gas contained 500 ppm NO, 5% O2, 500 ppm NH3 and N2 as the balance gas, and the pore velocity was 45000 h -1 The NH3-SCR activity of the catalyst was measured at a heating rate of 5°C / min. Under steady-state conditions, the reduction product was detected using a NOx analyzer, and its activity on NO was measured in the range of 150-600°C. x reduction activity.

[0038] Example 7 100 mg of the catalyst prepared in Examples 2 and 3 were respectively loaded into a fixed bed quartz reactor and dried at 150°C for 1 hour. The reaction raw gas contained 500 ppm NO, 5% O2, 500 ppm NH3, 5% H2O and N2 as the balance gas, and the pore velocity was 45000 h -1 The water resistance activity of the catalyst was measured at a heating rate of 5°C / min. x The analyzer detects the reduction product and determines its NO x reduction activity.

[0039] Example 8 100 mg of the catalyst prepared in Example 2 was loaded into a fixed bed quartz reactor and dried at 150°C for 1 hour. The reaction raw gas contained 500 ppm NO, 5% O2, 500 ppm NH3, 5% H2O and N2 as the balance gas, and the pore velocity was 45000 h -1 , the durability and stability of the catalyst were measured at 150°C.

[0040] Figure 1 The XRD diagram, H2-TPR and NH3-TPD curves of the zeolite catalyst obtained in Examples 1-3 are shown. It can be found that: XRD shows that the prepared material has the characteristic diffraction peak of ZSM-5 zeolite, and no diffraction peak of Cu element is detected, indicating that Cu is highly dispersed in the composite zeolite in the form of ions. The H2-TPR and NH3-TPD curves show that the redox property of pure ZSM-5 zeolite is relatively weak, but it has abundant acidic sites, while the zeolite modified by metal elements has obvious redox peaks.

[0041] Figure 2 and Figure 3 This is the electron microscope image of the composite zeolite Cu@ZSM-5 prepared in Example 2. It can be found that the prepared sample is composed of 300-500nm nanoparticles with regular morphology. The high-magnification TEM of the zeolite observes 1-3nm metal nanoclusters highly dispersed in the zeolite crystals, further suggesting that Cu ions are highly dispersed in the entire zeolite matrix.

[0042] Figure 4 a is the NH3-SCR activity of different samples prepared in Example 1; Figure 4 b is the NH3-SCR activity of different samples prepared in Examples 2, 4, and 5; Figure 4 c is the NH3-SCR activity of different samples prepared in Examples 2 and 3 in the presence of water vapor; Figure 4 Figure d is the stability test of the sample in the example. It can be found that the optimal Cu-modified composite catalyst has excellent NH3-SCR activity and can achieve 80% NO in a wide temperature window of 200-550°C. x Reduction of NO2 can be achieved at 225-450℃. x This is attributed to the combined effect of the high temperature activity of the acidic zeolite and the excellent low temperature catalytic oxidation activity of the metal elements. The catalytic activity decreases when the Cu content is too high, which may be attributed to the agglomeration of metal nanoclusters leading to the coverage of active sites. More importantly, this composite catalyst still has high catalytic activity in the presence of water vapor and can achieve 80% NH3 reduction at 200-500°C. At a temperature of 350°C, the composite catalyst has no significant effect on NO reduction in the presence of 2-8 vol% water.x The reduction performance can basically be maintained above 90%, suggesting its excellent water resistance and durability, which is related to the excellent thermal stability and hydrothermal stability of zeolite.

[0043] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, a person skilled in the art should understand that the specific implementation modes of the present invention can still be modified or replaced by equivalents, and any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be included in the scope of the claims.

Claims

1. An NH3-SCR catalyst, characterized in that: The NH3-SCR catalyst comprises: an acidic zeolite modified by a metal element; preferably, the metal element in the acidic zeolite modified by a metal element exists in the form of metal nanoclusters.

2. The NH3-SCR catalyst according to claim 1, characterized in that: The acidic zeolite includes TS-1, ZSM-5 or Beta zeolite.

3. The NH3-SCR catalyst according to claim 1, characterized in that: The metal element in the metal element-modified acidic zeolite is at least one of Fe, Cu, Mn and Zn, and the content of the metal element is 1.23-5.79 wt.%.

4. A method for preparing the NH3-SCR catalyst according to any one of claims 1 to 3, characterized in that: When the NH3-SCR catalyst is an acidic zeolite doped with metal elements, the preparation method comprises: dissolving one of a titanium source or an aluminum source, an inorganic silicon source, a metal element source, and an alkali metal salt in an aqueous solution containing a structure directing agent to obtain a mixed solution, performing a hydrothermal crystallization treatment, and then filtering, washing, drying, and calcining to obtain an acidic zeolite doped with metal elements.

5. The preparation method according to claim 4, characterized in that: include: (1) adding an inorganic silicon source and an alkali metal salt to an aqueous solution containing a structure directing agent to obtain a solution 1; (2) adding one of the titanium source or the aluminum source and the metal element source solution to water to obtain solution 2; (3) Solution 2 is added dropwise to solution 1 and stirred to mix, followed by hydrothermal crystallization treatment, and then filtered, washed, dried and calcined to obtain metal element-doped acidic zeolite.

6. A method for preparing the NH3-SCR catalyst according to any one of claims 1 to 3, characterized in that: When the NH3-SCR catalyst is an acidic zeolite modified by a metal element, the preparation method comprises: The acidic zeolite is added to an aqueous solution containing a metal element source and stirred to obtain a mixture; the obtained mixture is washed and centrifuged to remove the upper aqueous solution, and then dried and calcined to obtain the metal element modified acidic zeolite.

7. The preparation method according to claim 6, characterized in that: The preparation method of the acidic zeolite comprises: dissolving an inorganic silicon source, an aluminum source and an alkali metal salt in an aqueous solution containing a structure directing agent, performing a hydrothermal crystallization treatment, and then filtering, washing, drying and calcining to obtain the acidic zeolite.

8. The preparation method according to claim 4 or 6, characterized in that: The metal element source is at least one of ferrous chloride, cuprous chloride and zinc sulfate.

9. The preparation method according to claim 4 or 7, characterized in that: The structure directing agent is one of tetraethylammonium hydroxide (TPAOH) and tetraethylammonium hydroxide (TEAOH).

10. The preparation method according to claim 4 or 7, characterized in that: The silicon source is one of ethyl orthosilicate, orthosilicic acid, and sodium silicate; The aluminum source is one of aluminum sulfate, aluminum chloride, and metaaluminate; The alkali metal salt is one of sodium chloride and potassium chloride.

11. The preparation method according to claim 4, characterized in that: The concentration of the alkali metal salt in the mixed solution is 1 to 3 mg / mL; The concentration of the metal element in the mixed solution is 10 to 100 mg / mL; The Si / Al atomic ratio in the zeolite precursor solution in the mixed solution is 10 to 100; The temperature of the hydrothermal crystallization is 100 to 220° C., and the time of the hydrothermal crystallization is 12 to 24 hours.

12. The preparation method according to claim 4 or 7, characterized in that: The drying temperature is 80-120° C.; the calcining temperature is 500-600° C., and the calcining time is 4-8 hours.

13. Use of the NH3-SCR catalyst according to any one of claims 1 to 3 in automobile exhaust purification.